Cytotoxicity, proliferation and migration rate assessments of human dermal fibroblast adult cells using Zingiber zerumbet extract - Mazlyzam Abdul Latif,; Farah Wahida Ibrahim,; Siti Aisyah Arshad,; Chua, Kien Hui; Nurul Farhana Jufri,; Asmah Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Zingiber zerumbet is a plant that is traditionally consumed in many countries, including Malaysia due to its therapeutic properties. Previously it has been proven to inhibit migration and proliferation of cancer cells. However, its effects on normal cells are still unknown and would be the main focus of this study. The cytotoxicity along with proliferation and migration activities were evaluated against human dermal fibroblast adult cell line (HDF-a) using MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium], proliferation and scratch assays. The cytotoxicity effect was determined following 24 h of treatment by ethyl acetate Z. zerumbet extracts while proliferation assay was conducted at different concentrations (500, 750, 1000, 1250 and 1500 μg/mL) at 24, 48 and 72 h. The cell migration rate was determined by scratch assay in 6-well culture plate using 10 μL pipette tip following 80% confluency at optimum concentration (750 μg/mL) of Z. zerumbet at different time points. Migration rate was scored at every 24 h using digital camera connected to the inverted microscope. The results from cytotoxicity test showed no IC50 values were observed for Z. zerumbet extract as compared to the positive control (menadione). Proliferation assay exhibited highest cell viability (137%) at 750 μg/mL. The rate of cell migration increased following treatment with Z. zerumbet extract after 48 h. However, the result was not significantly different when compared to the control. In conclusion, Z. zerumbet ethyl acetate extract is able to induce cell proliferation and potentially promoting migration rate of wound healing in in-vitro model.